Promoting TT's National Instrument - The Pan - Unknown (Newsday)
This article examines "Panman Pat", born Pat McNeilly, a performer, author and teacher of the Trinidad and Tobago's national instrument, the steelpan in Canada. Panman Pat has been teaching steelband as a curriculum course in Toronto for the past 12 years and is looking forward to exploring the issue of curriculum development and teaching of the steelband in high schools in Trinidad and Tobago.
Keywords: Steel bands (Music) -- Study and teaching; Steel band music -- Canada; Musicians -- Trinidad and Tobago; Steel drum (Musical instrument) -- Instruction and study -- Trinidad and Tobago